Interactions between zooplankton grazers and phytoplankton as part of the energy and nutrient dynamics in the Swan River Estuary, Western Australia - Griffin, Sandra Lenore (Curtin University, 2003)
Most Australian studies on estuarine plankton have examined distribution and abundance in relation to hydrological changes, primary productivity and associated nutrient dynamics. Relatively few have examined the complex interactions between zooplankton grazers and the type and quality of food available, or the role of zooplankton grazers in structuring phytoplankton communities, or their contribution to the nutrient pool. The ecological role of zooplankton grazers in the Swan River estuary, Perth, Western Australia, was examined as part of a collaborative research project directed by the Western Australian Estuarine Research Foundation, which was established in response to concern about increasing intensity and persistence of algal blooms. The present study focussed on one component of the zooplankton, the Copepoda, as model zooplankton grazers. A regular zooplankton monitoring programme, undertaken over a two year period, provided data on seasonal patterns of abundance and distribution of zooplankton over a broad spectrum of physical conditions. Relationships were identified between habitat variables, such as algal biomass, dissolved oxygen, salinity and suspended solids and zooplankton distribution, relative abundance and species composition. Prior to the inception of this study, it was assumed that copepod species composition, abundance and richness in the Swan River estuary may have changed over time, in response to long-term declines in water quality. Comparison of historical copepod monitoring data with current data did not detect any such change and it was concluded that there was greater variation in copepod species composition, abundance and richness within years than between years and that no significant change had occurred between 1966 and 1997.However, an absence or reduction in abundance of copepods in areas of very high algal biomass (>80 pg chlorophyll a.L-1) suggests that local loss of water quality may have an impact on copepods over a small spatial scale within the estuary. Different aspects of the interactions between zooplankton grazers and phytoplankton were studied. Zooplankton grazing rates were measured in situ during algal blooms and in the laboratory under controlled conditions to determine the potential for zooplankton grazers to reduce algal biomass. Field and laboratory experiments supported the hypothesis that copepods and other zooplankton can exert 'top-down control' over phytoplankton biomass, but that the type and biomass of phytoplankton present affected their ability to exert this control. The results of the field and laboratory grazing experiments, along with literature data, were used to provide input data for a model of zooplankton and phytoplankton dynamics during a dinoflagellate bloom in the Swan River estuary. The model was tested against biomass measurements of zooplankton and phytoplankton to determine how well it predicted actual changes in the plankton community. The simulated output closely followed the measured Page x field data and fitted regression curves and provided information about diurnal patterns of phytoplankton production, respiration and migration and hydrodynamic transport, which was not available from field data. It was shown that zooplankton grazing, particularly grazing by microzooplankton, was the process contributing most to the observed decline in dinoflagellate biomass. Nutrient availability is one of several factors determining productivity of phytoplankton. Nutrients within copepod faecal pellets are relocated by faecal deposition to sediments, where microbial activity leads to the remineralisation of these nutrients.Quantification of metabolic excretion of nutrients by copepods and the rate at which pellets are produced by copepod grazers, the concentration of nutrients within faecal pellets and the rate at which these nutrients are released indicated that copepods may play an important role in nutrient regeneration during summer and autumn when allochthonous nutrients are unavailable. At other times of the year, it is unlikely that copepods play an important role in nutrient regeneration. The research has provided a more detailed level of understanding of the interactions between zooplankton, phytoplankton and their environment. The data is ideally suited for use in a computer model to predict the effects of management actions on the Swan River estuary. This would allow pre-emptive management strategies to be developed and lessen the focus on reactive management.